ANALISIS MAKNA SUPERSTISI KATEGORI MATA PENCAHARIAN DAN HUBUNGAN SOSIAL PADA MASYARAKAT MELAYU RUMBAI - Sri Setiarti; Erni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Superstition is a belief that is believed and can be proven logically and also does not necessarily happen. In this study, researchers conducted research in one of the villages in East Rumbai District, namely in the village of Tebing Tinggi Okura. The researcher conducted this research based on a deeper curiosity about the connotative and denotative meanings of the superstitions of the East Rumbai Malay community, this superstition will later lead to the values ​​of people's trust in living life in their environment, this research helps the community teach moral teachings to children and youth, so that it can be carried out in everyday life. Because this superstition is very closely related to the customs and culture of the Malay people and is the legacy of their ancestors. This study aims to analyze a meaning related to the formulation of the problem, namely the superstitious meaning of livelihoods and social relations in the East Rumbai Malay community in the village of Tebing Tinggi Okura. Researchers used a qualitative descriptive method with a type of field research, with a qualitative approach. Researchers used three stages in analyzing data, namely data editing, data presentation, and drawing conclusions. The results of the study found 27 denotative and connotative meaning data. The results of the analysis found by the author can draw the conclusion that the superstition found in a Rumbai Malay community contains denotative and connotative meanings. In Malay society, especially the oldest people for generations, apply superstition in daily life because the use of superstitious can regulate the norms in society, especially in livelihoods and social relations.